Antioxidant action and protective and reparative effects of lentinan on oxidative damage in HaCaT cells. (23rd February 2018) - Zi, Yusha; Zhang, Bo; Jiang, Biao; Yang, Xingyao; Liang, Zilu; Liu, Weiyi; He, Congfen; Liu, Lei
Summary: Background: Lentinus edodes is one of the largest edible fungi. Lentinan, extracted from its fruiting body has clinically significant anticancer, antibacterial, antiviral, and anticoagulant effects; however, its preventive effects on skin oxidative damage are unclear. Aims: We aimed to evaluate the in vitro antioxidation capability of lentinan and its protective and reparative effects on a model of cell oxidative damage. Methods: We evaluated the in vitro antioxidant potential of lentinan by assessing its free‐radical quenching ability using DPPH and ABTS and superoxide anions. Using the HaCaT cell line as the experimental system, we tested the protective and reparative effects of lentinan on a model of H2 O2 ‐induced cellular oxidative damage through assessment of cell survival rate, malondialdehyde (MDA) content, and superoxide dismutase (SOD) activity. Results: Lentinan displayed high antioxidant potential: DDPH and ABTS quenching rates were above 60%; superoxide anions, approximately 18%. Furthermore, lentinan could dose‐dependently prevent the reduction of activity in HaCaT cells by H2 O2, reduce MDA formation, and increase SOD activity. Moreover, lentinan showed not only a protective effect against oxidative damage but also reparative effects to a certain extent, in HaCaT cells. Conclusions: Our findings demonstrated the ability of lentinan to enhance cellular tolerance to oxidative damage, stress resistance, and to have protective and reparative effects on damaged cells. Therefore, with L. edodes as a source for antiaging substances, cosmetics with homology to foods have great potential clinical applications.